PHONOLOGICAL ACQUISITION AND INNOVATION OF THE SERANG JAVA LANGUAGE IN SERANG DISTRICT - Juanto, Ade; Nedi Kurnaedi; Wati Anggraeni; Hilda Mulda Ningsih; Yuyun Yunengsih; Husnul Khotimah; Yanwar Samsul Akmal (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
The aims of this research include, among other things, to describe the use of the Serang Javanese language used in Serang Regency, differentiate the use of native Javanese from Javanese in Serang Regency, and explain the factors that influence the phonological dialect in Serang Regency. The research carried out is a type of qualitative research, this research requires descriptive data in the form of words and utterances from the object being studied. From the results that have been carefully studied between the two languages, namely Javanese Serang and Javanese Krama Inggil, the two clearly have quite a comparison, for example in the use of vowels, the pitch of the voice and the softness of the tone used. The use of the Krama Inggill Javanese accent is smoother and easier to hear, while the standard Serang Javanese language is rougher. Apart from that, words that end in consonants in Serang Javanese are read in full, for example the word